Implications of AAOE observations for proposed chemical explanations of the seasonal and interannual behavior of Antarctic ozone - Ko, M. K. W.; Rodriguez, J. M.; Sze, N. D.; Proffitt, M. H.; Starr, W. L.; Krueger, A.; Browell, E. V.; Mccormick, M. P. (1989)
Model simulations were used to investigate the seasonal and interannual behavior of ozone for different choices of initial odd nitrogen concentration in July and different assumptions on the heterogeneous reactions, with particular consideration given to the possible contribution of chlorine chemistry to the ozone hole phenomenon. The numerical experiments were selected based on the simulations of the observed trace gas concentrations during the Airborne Antarctic Ozone Experiment in 1987. In all cases considered, the catalytic cycle associated with the formation and photolysis of Cl2O2 could account for more than half of the photochemical removal of O3 within the Antarctic vortex through mid-September. The reaction of BrO with ClO, which accounts for 15-20 percent of O3 removal in the same period, tends to play a more important role toward the end of September, when the concentration of ClO is expected to decrease. No simple relationship was found between the increase in chlorine lavel and the interannual decrease in Antarctic O3.